2014
DOI: 10.3389/fnins.2014.00375
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cognitive decline: role of inflammation and vascular changes

Abstract: The incidence of obesity in middle age is increasing markedly, and in parallel the prevalence of metabolic disorders including cardiovascular disease and type II diabetes is also rising. Numerous studies have demonstrated that both obesity and metabolic disorders are associated with poorer cognitive performance, cognitive decline, and dementia. In this review we discuss the effects of obesity on cognitive performance, including both clinical and preclinical observations, and discuss some of the potential mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
260
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(276 citation statements)
references
References 145 publications
10
260
1
5
Order By: Relevance
“…43 Low-grade systemic inflammation with overproduction of inflammatory cytokines in individuals with IR 44 can contribute to cognitive decline and dementia. 45 Interleukin (IL)-1b and IL-6 have been found to disrupt neural circuits involved in cognition and memory 46,47 and elevated plasma levels of IL-6 and IL-12 levels associated with impaired processing speed and executive function at the Stroop Interference and digit symbol testing in a group of elderly participants. 48 A recent meta-analysis confirmed the association between raised levels of CRP and IL-6 and increased risk of dementia.…”
Section: Figurementioning
confidence: 99%
“…43 Low-grade systemic inflammation with overproduction of inflammatory cytokines in individuals with IR 44 can contribute to cognitive decline and dementia. 45 Interleukin (IL)-1b and IL-6 have been found to disrupt neural circuits involved in cognition and memory 46,47 and elevated plasma levels of IL-6 and IL-12 levels associated with impaired processing speed and executive function at the Stroop Interference and digit symbol testing in a group of elderly participants. 48 A recent meta-analysis confirmed the association between raised levels of CRP and IL-6 and increased risk of dementia.…”
Section: Figurementioning
confidence: 99%
“…Salthouse in 2009 reported that the declination of cognitive function in healthy educated adults begin in 20 years or early 30 years. The middle-age people with obesity recalled less number of words measured by the word-list learning test than normal (Nguyen, Killcross, & Jenkins, 2014). They spent more time to complete digitsymbol substitution test than normal (Cournot et.…”
Section: Introductionmentioning
confidence: 92%
“…Cognitive function may be partially modifiable via lifestyle behaviors. For instance, certain health characteristics, such as physical activity [5][6][7], smoking [8], and weight status [9], have all been shown to be individually associated with cognitive function.…”
Section: Introductionmentioning
confidence: 99%